Management of generalized malignant lymphomata with "systemic" radiotherapy. - Johnson, R. E. (Nature Publishing Group, 1975)
The natural history of lymphocytic lymphomata is such that anatomical generalization of disease is usually present at the time of diagnosis. Tumour infiltration of extralymphatic sites such as the liver and bone marrow is identifiable with particular frequency in those cases presenting with lymph node manifestations of disease. Even in the absence of detectable extralymphatic dissemination, the lymphatic involvement is often sufficiently diffuse to mitigate against extensive lymph node irradiation "Ã  la Hodgkin's disease" as appropriate or technically feasible form of treatment. Rather, systemic treatment must be recognized as imperative for the majority of newly diagnosed patients and we have investigated "systemic" radiotherapy as an alternative to chemotherapy during the past decade. Our experience with 57 consecutive patients with lymphocytic lymphoma has been reviewed. Total body irradiation (TBI) has been found to yield high remission rates despite a lack of serious toxicity or constitutional reactions. Rigorous diagnostic staging was not employed but despite the advanced stage of disease which was clinically obvious in most cases, survival rates have been strikingly high. Actuarially calculated 5-year survival rates for the well differentiated (diffuse and nodular combined), nodular poorly differentiated and diffuse poorly differentiated subtypes are 85%, 69% and 51% respectively. Furthermore, initial management with radio-therapy as described has not negated with effective use of subsequent chemotherapy when selectively required.